Kepemimpinan Pendidikan Islam Berdasarkan Perspektif Muhammadiyah - Rivadah, Migfar; Rahmandhani, Muhamad Arya; Nurfadila, Nurfadila; Hidayat, Ma’rif (Lembaga Yasin AlSys, 2022)
This study aims to find out how leadership plays a major, centered and very vital role in the formation of a good institution, especially in Islamic educational institutions. Muhammadiyah is an Islamic organization founded by KH Ahmad Dahlan who has a desire to create an Islamic educational institution that aims to form a noble character and a good scientific mindset. From there, Muhammadiyah has the view of one of the leaders of Muhammadiyah, namely KH. AR Fakhrudin about leaders who have Islamic character who are not selfish, arrogant and become role models for the best Islamic education leadership to run. The research that we use is qualitative research which uses a descriptive approach with library research, the method used is to analyze the existing literature systematically such as articles, books, journals, and documents related to the problems discussed.